Factors Influencing Implementation of Rural Electrification Programme in Kenya: A Case of Kieni East Sub County, Nyeri County - Kareithi, Rosemary; Muhua, George (European Scientific Journal, ESJ, 2018)
The Government of Kenya through numerous policies and programmes have come up with the rural electrification programmes which is to play a crucial role in the provision of electricity to rural areas in a bid to spur human, social and economic development in the Country. The purpose of this study was to determine the factors influencing the implementation of rural electrification programme in Kieni East Sub County, Nyeri County. The study adopted a descriptive survey research design. The target population of the study was 4289 households and 10 Rural Electrification Authority Team in Kieni East Sub County. Simple random sampling and Purposive sampling was used to select a sample of 94 households and 5 Rural Electrification Authority Officials. The data was collected through structured questionnaires. Reliability of the questionnaires and validity was tested through piloting. Ethics in research was observed and responses were handled with utmost confidentiality, while the study ensured fair gender representation of respondents. The data was analyzed using through descriptives and presented through tables and graphs. The study found that funding, cost of electricity, alternative sources of power and demand affected implementation of Rural Electrification Programme to a great extent. Thus, these factors play a key role in determining the success of the implementation of Rural Electrification Programme in Kieni East Sub County. The study recommended that subsidizing of consumer connections cost, wiring material cost and unit cost of energy should be lowered and also provision of incentives for investments in alternative power sources such as allocation of sufficient funds and timely disbursement for implementation of grid extension in Kieni East should be encouraged by involving policy makers and the government in formulation of policies favorable for the implementation of Rural Electrification Programme in rural areas of Kenya. The study suggests that further studies should be carried out on the influence of institutional factors on the implementation of rural electrification programs in Kenya.